Expression of cardiac inwardly rectifying potassium channels in pentylenetetrazole kindling model of epilepsy in rats - MEGA TİBER, PINAR (C M B ASSOC, 2018)
Clinical and experimental studies show that epilepsy affects cardiac function; however, the underlying molecular mechanism has not been fully elucidated. Inwardly-rectifying potassium (Kir) channels transport K+ ions into excitable cells such as neurons and cardiomyocytes; they control the cell excitability by acting towards the repolarization phase of cardiac action potential. Kir channel expression has been previously shown to vary in epileptic brains, at the same time seizures are known to affect the autonomic nervous system. Kir channel expression in cardiac tissue is a possible mechanism for the explanation of cardiac pathology in epilepsy. We investigate the expression of Kir channels in epileptic cardiac tissue by using pentylenetetrazole (PTZ)-kindling model in rats. Our molecular analyses showed significant decrease in cardiac Kir channel mRNA and protein expression of PTZ-kindled rats. Interestingly, both Kir2.x, which directs I-K1 flux in ventricular tissue and Kir3.x, which is responsible for I-KACh in the atria, were observed to decrease significantly. Kir channel expression also differs between females and males. This is the first study to our knowledge in epileptic cardiac tissue showing the expression of Kir channels. Our results show that Kir channels may play a role in cardiac pathology associated with epilepsy.
Keywords: Epilepsy; Kir channels; Heart; Rats; Protein and gene expression; SUDDEN UNEXPLAINED DEATH; HEART-RATE-VARIABILITY; UNEXPECTED DEATH; DYSFUNCTION; CONSEQUENCES; SEIZURES; REVEALS; KIR2; HCN